ANALISIS ISU-ISU DAN PERKEMBANGAN PENILAIAN DI SDN 13 BATU GADANG - Sunefti, Aida; Desmita, Imit; Ananta, Louisa; Ridho; Adila, Zahra; Reinita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This article aims to provide a comprehensive description of the implementation of assessment in the Merdeka Curriculum at the elementary school level, specifically at SDN 13 Batu Gadang. Assessment in the context of elementary school education has undergone a paradigm shift from an outcome-oriented approach to one that emphasizes the learning process. This study employs a descriptive qualitative approach, using data collection techniques such as observation and semi-structured interviews with teachers. The findings indicate that assessment has been implemented more comprehensively, covering cognitive, affective, and psychomotor aspects through various methods such as observation, projects, portfolios, as well as oral and written tests. In addition, the use of technology in assessment has begun to have a positive impact on improving efficiency, accuracy, and ease of data management. Assessment also encourages students’ active engagement in learning, making it more meaningful. However, the implementation of assessment still faces various challenges, such as time constraints, difficulties in developing assessment instruments, and teachers’ insufficient understanding of authentic assessment. Therefore, continuous training and the enhancement of digital literacy are necessary to support the optimization of assessment implementation. It is hoped that the results of this study will contribute to the development of a more effective, contextual, and student-centered assessment system.